Binary Lithium Indides Li22–xIn8+x (x = 0.1), Li11–xIn4+x (x = 1.05), and Li10–xIn2+x (x = 1.59) with Clusters. Issue 12 (11th March 2014) - Chumak, Ihor; Pavlyuk, Volodymyr; Ehrenberg, Helmut
Abstract: The synthesis, structural characterization, and chemical bonding peculiarities of three new binary Li–In intermetallides are reported. The crystal structures of these compounds were determined by single‐crystal X‐ray diffraction analysis. The compositions obtained after structure refinements were Li22– x In8+ x ( x = 0.1) [new structure type, monoclinic crystal system, Pearson symbol mS30, space group C2 / m, a = 14.156(3), b = 4.729(1), c = 8.617(2) Å, β = 105.89(1)°, R1 = 0.0279, wR2 = 0.0583 for 669 reflections], Li11– x In4+ x ( x = 1.05) [new structure type, trigonal, P 3 m1, hP15, a = 4.7480(7), c = 14.283(3) Å, R1 = 0.0323, wR2 = 0.0741 for 277 reflections], and Li10– x In2+ x ( x = 1.59) [new structure type, hexagonal, P6 / mmm, hP12, a = 4.6975(7), c = 11.526(2) Å, R1 = 0.0680, wR2 = 0.1358 for 127 reflections]. The Li22– x In8+ x ( x = 0.1) structure is related to the structure of lithium (W‐type). The structure of Li11– x In4+ x ( x = 1.05) can be described as a derivative of the CdI2 type. Li10– x In2+ x ( x = 1.59) can be derived from the Li2 Pt structure. [In2 @Li20 ] clusters composed of 20 lithium atoms, which surround a In–In pair, are detected in the structure of all three investigated compounds. TB‐LMTO (Tight‐Binding Linear Muffin‐Tin Orbital) calculations indicate strong covalent In–In interactions and the presence of [In2 @Li20 ] clusters in these new binary indides. Abstract : Three new binary lithium indides were synthesized, and their crystal structures were studied by single‐crystal X‐ray diffraction analyses. All compounds crystallize in new structure types. The presence of [In2 @Li20 ] clusters was detected in the structure of all three new compounds. The covalent type of the In–In bonding in the clusters was confirmed by electronic structure calculations.